2017
DOI: 10.1177/1178630217704194
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues in Commercial Lettuce, Onion, and Potato Samples From Bolivia—A Threat to Public Health?

Abstract: Bolivia does not have a surveillance program for pesticide residues in food. The few published studies have suggested that pesticide contamination in food may present a public health problem. Data are lacking for all foods except tomatoes and breast milk. In this study 10 potato, 10 onion, and 10 lettuce samples from La Paz were sampled on August 15, 2015 at a local market and screened for 283 pesticides. Residues of cypermethrin, chlorpyrifos, difenoconazol, or/and λ-cyhalothrin were detected in 50% of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…All analytes were determined in a single injection. This validation results are comparable with the reports by Skovgaard et al (2017), who implemented a GC-MS method for the analysis of pesticides in crop samples (lettuce, onion and potatoes), with a detection limit of 3 µg kg -1 , a limit of quantification of 10 µg kg -1 and a recovery between 70% and 120%. Guan et al, (2014) reported the validation of the LC-MS / MS method for the determination of pesticides in onion, garlic and leek, with a detection limit between 1 to 10 µg kg -1 and a recovery percentage between 70.1% and 109.7%.…”
Section: Recovery For Organochlorine and Organophosphorus Pesticidessupporting
confidence: 87%
“…All analytes were determined in a single injection. This validation results are comparable with the reports by Skovgaard et al (2017), who implemented a GC-MS method for the analysis of pesticides in crop samples (lettuce, onion and potatoes), with a detection limit of 3 µg kg -1 , a limit of quantification of 10 µg kg -1 and a recovery between 70% and 120%. Guan et al, (2014) reported the validation of the LC-MS / MS method for the determination of pesticides in onion, garlic and leek, with a detection limit between 1 to 10 µg kg -1 and a recovery percentage between 70.1% and 109.7%.…”
Section: Recovery For Organochlorine and Organophosphorus Pesticidessupporting
confidence: 87%
“…Baby leaf lettuce is widely cultivated in Italy under both open field and greenhouse conditions [1]. Baby leaf vegetables are characterized by a short cycle but it requires a correct agronomic management to avoid high levels of nitrate accumulation and pesticide residues in the final product [2]. Therefore, there is a paramount interest in enhancing its production and quality, and at the same time reducing the nitrate levels of leafy vegetables, in order to overcome the legal limit for the marketing imposed by the European Community (Reg.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of growing season on leafy lettuce yield and quality was more pronounced than the effect of nutrient solution composition (Fallovo et al, 2009). Additionally the proper mineral nutrition and chemical protection of lettuce is difficult because of short vegetation period and risk of high level of nitrate concentration and pesticide residues (Skovgaard et al, 2017).…”
Section: Biological Materialsmentioning
confidence: 99%